Effectiveness of school-based interventions in delaying sexual debut among adolescents in sub-Saharan Africa: a protocol for a systematic review and meta-analysis. Issue 5 (21st May 2021) - Maina, Beatrice W; Juma, Kenneth; Igonya, Emmy Kageha; Osindo, Jane; Wao, Hesborn; Kabiru, Caroline W
Abstract : Introduction: Early sexual debut is associated with poor sexual and reproductive health outcomes across the life course. A majority of interventions aimed at delaying sexual debut among adolescents in sub-Saharan Africa (SSA) have been implemented in schools with mixed findings on the effectiveness of such interventions. This systematic review will summarise and synthesise existing evidence on the effectiveness of school-based interventions in delaying sexual debut among adolescents aged 10–19 years. Methods and analysis: We will conduct a comprehensive database search of peer-reviewed studies published in PubMed, Scopus, Science Direct, Web of Science, HINARI and EBSCO (PsycINFO, Global Health, CINAHL) and in Cochrane library, National Institute of Health and Turning Research into Practice databases for ongoing studies yet to be published. All studies conducted in SSA between January 2009 and December 2020, regardless of the study design, will be included. Two authors will independently screen all retrieved records and relevant data on sexual debut extracted. Data will be pooled using the random effects model. Dichotomous outcomes will be reported as risk ratios and continuous data as mean difference at 95% CI. Heterogeneity will be assessed using the I² statistic. Findings will be presented in tables and charts, while providing a description of all included studies, themes and concepts drawn from literature. Ethics and dissemination: Ethical approval is not required. The findings will be disseminated through peer-reviewed publications, presentations at relevant conferences and other convening focusing on adolescent sexual and reproductive health.